KOMPOSISI MEDIA TANAM DAN DOSIS PUPUK NPK TERHADAP TUMBUHAN DAN HASIL TANAMAN TERUNG (Solanum melongena L.) - Bayu Saputro Aji, Adi; Puspitorini, Palupi; Serdani, Army Dita; Widiatmanta , Jeka; Wibowo, Agung Setya (grafting, 2024)
Eggplant is a horticultural crop that is very important for society. One effort to increase production is by providing soil, manure and NPK fertilizer. This research aims to determine the effect of planting media and NPK fertilizer on the growth and yield of eggplant (Solanum melongena L.) variety Mustang F1. This research was conducted in Krajan Hamlet, Kebonsari Village, Kademangan District, Blitar Regency, East Java Province in February-April 2023. The research was prepared using (RAK) factorial with two factors, namely the composition of the planting media (M) and the dose of NPK fertilizer (D). Each treatment had 3 repetitions. Observations will be carried out after 10 days after planting, with an observation interval of 20 days, the observation parameters include plant height, stem base diameter, fruit diameter, and fruit weight. The research results showed that the combination treatment between the composition of the planting media and the dose of NPK fertilizer had a significant effect on plant height, stem base diameter, fruit diameter and fruit weight.